The Effect of Dietary and Exercise Self-Management Support Program on Dietary Behavior Exercise Behavior and Clinical Outcomes in Muslim Patients with Poorly Controlled Type 2 DM in a Community Setting in Indonesia - Pamungkas, Rian Adi; Chinnawong, Tippamas; Kritpracha, Charuwan (Department of Nursing, Faculty of Medicine, Diponegoro University, 2015)
Purpose: The objective of this study was to examine the effect of dietary and exercise self-management support program on the dietary behavior, exercise behavior, and clinical outcomes of Muslim patients with poorly controlled type 2 DM in Indonesia. Methods: This study was a quasi-experimental, two group, pre-test and post-test design. The experimental group received the dietary and exercise self-management support program and usual care, whereas the control group only received the usual nursing care.Result: 35 subjects in the experimental group and 35 subjects in the control group completed the program, respectively. The findings indicated that there are significantly differences in dietary behavior (p=.00), exercise behavior (p=.00) and clinical outcomes: fasting blood glucose (FBG) (p=.00), cholesterol total level (p=.01) and systolic blood pressure (p=.00) between the experimental group and control group. However, for the BMI status (p=.84) and diastolic blood pressure (BP) (p=.32) were no significant differences between two groups. Conclusion: The dietary and exercise self-management support program was effective for improving the dietary behavior, exercise behavior, FBG, and total cholesterol level for individuals with poorly controlled type 2 diabetes mellitus. Further studies should be replicated using larger groups over a longer time frame.